(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
Many 18th-century documents—separation or reconciliation agreements, divorce rulings, wills, dowry lists, and litigation records regarding estates—highlight the views held by ordinary people regarding private life, the life of a couple, family behavior, the status of women, and so on. Each document is a tiny narrative, a "micro-history" featuring a man and his problems as the central figure. These "tiny narratives" offer a better understanding of the human personality—one that is both representative of and exceptional within a given sociocultural context. Through these long-forgotten and neglected "micro-histories," the aim is to "humanize" the past.